PrEdiction of Risk and Communication of outcomE followIng major lower limb amputation: a collaboratiVE study (PERCEIVE)—protocol for the PERCEIVE qualitative study. Issue 1 (17th January 2022) - Milosevic, Sarah; Brookes-Howell, Lucy; Gwilym, Brenig Llwyd; Waldron, Cherry-Ann; Thomas-Jones, Emma; Preece, Ryan; Pallmann, Philip; Harris, Debbie; Massey, Ian; Stewart, Philippa; Samuel, Katie; Jones, Sian; et al.
Abstract : Introduction: Deciding whether to proceed with a major lower limb amputation is life-changing and complex, and it is crucial that the right decision is made at the right time. However, medical specialists are known to poorly predict risk when assessing patients for major surgery, and there is little guidance and research regarding decisions about amputation. The process of shared decision-making between doctors and patients during surgical consultations is also little understood. Therefore, the aim of this study is to analyse in depth the communication, consent, risk prediction and decision-making process in relation to major lower limb amputation. Methods and analysis: Consultations between patients and surgeons at which major lower limb amputation is discussed will be audio-recorded for 10–15 patients. Semi-structured follow-up interviews with patients (and relatives/carers) will then be conducted at two time points: as soon as possible/appropriate after a decision has been reached regarding surgery, and approximately 6 months later. Semi-structured interviews will also be conducted with 10–15 healthcare professionals working in the UK National Health Service (NHS) involved in amputation decision-making. This will include surgeons, anaesthetists and specialist physiotherapists at 2–4 NHS Health Boards/Trusts in Wales and England. Discourse analysis will be used to analyse the recorded consultations; interviews will be analysed thematically. Finally, workshops will be held with patients and healthcare professionals to help synthesise and interpret findings. Ethics and dissemination: The study has been approved by Wales REC 7 (20/WA/0351). Study findings will be published in international peer-reviewed journal(s) and presented at national and international scientific meetings. Findings will also be disseminated to a wide NHS and lay audience via presentations at meetings and written summaries for key stakeholder groups.